Motivations and barriers to electric bike use in the U.S.: views from online forum participants. Issue 2 (3rd May 2020) - Mayer, Adam
ABSTRACT: Electric bikes (ebikes) are an emerging technology that can partially mitigate many of the challenges facing the United States, such as improving mobility for the elderly and disabled, by mitigating diabetes and obesity, and reducing greenhouse gas emissions. Although ebikes have become increasingly common in the U.S., they have failed to gain significant market penetration despite their great promise. In this paper, we present the results of semi-structured interviews with 47 ebike users from around the U.S. to understand motivations and barriers to ebike use. Following prior research, our results suggest that cost savings and health benefits are the primary motivations behind ebike adoption, while lack of infrastructure is the primary impediment to ebike usage. Other barriers to ebike usage include shaming (primarily from other cyclists) and unwelcoming local policy environments.